Adverse effects of monoclonal antibodies in the treatment of moderate-to-severe asthma: a narrative review - Izabela Orzołek; Izabela Stawicka; Jakub Jarmołowicz; Agata Boczar; Patryk Dryja (Journal of Education, Health and Sport)
Introduction and purpose: Over the past two decades, the management of severe asthma shifted from high doses of inhaled and oral corticosteroids to targeted biologic agents. Adverse effects of treatment with monoclonal antibodies are not yet fully characterised. The aim of this paper is to provide a comprehensive review of the adverse effects of the FDA-approved monoclonal antibodies in the treatment of moderate-to-severe asthma, including omalizumab, benralizumab, dupilumab, mepolizumab, reslizumab, tezepelumab.